Pengaruh Return On Assets (ROA Terhadap Harga Saham dengan Earning Per Share (EPS) sebagai Intervening (Studi Kasus pada Perusahaan Sub Sektor Tekstil dan Garmen yang terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Fiona Mutiara Efendi; Ngatno Ngatno (Universitas Diponegoro, 2018)
The rapid development of capital markets are now attracting the attention of people and capital owners to invest in capital markets. During the year 2013-2016 the average stock price of the textile and garment enterprises sub-sector experienced a fluctuating condition. The financial ratios that are suspected to affect the ups and downs of stock prices are ROA and EPS. The population of this research are 15 Textile and Garment Sub-Sector Companies listed on Indonesia Stock Exchange in 2013-2016. The analysis technique used is linear regression analysis with SPSS program. This study aims to determine the effect of ROA on stock prices through EPS as a mediator. The results showed that ROA has no significant effect on stock prices, but ROA has a significant influence on the mediation variable that is EPS. EPS variable has positive and significant effect to stock price. ROA and EPS have a significant effect on stock prices. EPS is fully mediated variable and can significantly mediate the relationship between ROA and stock prices. Based on the analysis results, can be concluded that the variables that affect the stock price is EPS, while the ROA variable does not affect the stock price. As well as EPS variables can mediated the relationship between ROA and stock prices. The results of this research, it is expected the company further increase the profitability of the company in order to increase the stock price so that it can give benefit the company and investors.